Cell cycle regulated DNA methyltransferase: fluorescent tracking of a DNA strand-separation mechanism and identification of the responsible protein motif. Issue 20 (14th October 2020) - Konttinen, Olivia; Carmody, Jason; Pathuri, Sarath; Anderson, Kyle; Zhou, Xiaofeng; Reich, Norbert
Abstract: DNA adenine methylation by Caulobacter crescentus C ell C ycle R egulated M ethyltransferase (CcrM) is an important epigenetic regulator of gene expression. The recent CcrM-DNA cocrystal structure shows the CcrM dimer disrupts four of the five base pairs of the (5′-GANTC-3′) recognition site. We developed a fluorescence-based assay by which Pyrrolo-dC tracks the strand separation event. Placement of Pyrrolo-dC within the DNA recognition site results in a fluorescence increase when CcrM binds. Non-cognate sequences display little to no fluorescence changes, showing that strand separation is a specificity determinant. Conserved residues in the C-terminal segment interact with the phospho-sugar backbone of the non-target strand. Replacement of these residues with alanine results in decreased methylation activity and changes in strand separation. The DNA recognition mechanism appears to occur with the Type II M.HinfI DNA methyltransferase and an ortholog of CcrM, BabI, but not with DNA methyltransferases that lack the conserved C-terminal segment. The C-terminal segment is found broadly in N4/N6-adenine DNA methyltransferases, some of which are human pathogens, across three Proteobacteria classes, three other phyla and in Thermoplasma acidophilum, an Archaea. This Pyrrolo-dC strand separation assay should be useful for the study of other enzymes which likely rely on a strand separation mechanism.